Pengaruh Harga Kualitas Produk dan Brand Image Terhadap Keputusan Pembelian pada Sepatu Converse - Nadhif Andika Dwi Putra; M. Sihab Ridwan (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This thesis discusses the influence of price, product quality, and brand image on purchasing decisions for Converse shoes. The purpose of this study is to identify, prove, and analyze the effects of price, product quality, and brand image on the purchase decisions of Converse shoes among students of Universitas 17 Agustus 1945 Surabaya.Using a quantitative approach, the research collects both primary and secondary data from 100 respondents. The analytical method employed is multiple linear regression analysis, which includes validity tests, reliability tests, and classical assumption tests to analyze the data.The results of the study show that partially, price, product quality, and brand image each have a significant influence on purchasing decisions. Simultaneously, price, product quality, and brand image also significantly influence purchasing decisions. These findings highlight the importance of these three factors in marketing strategies to increase consumer buying interest